2021
DOI: 10.1038/s41467-021-27406-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the chirality of carbon nanodots on their interaction with proteins and cells

Huijie Yan,
Michele Cacioppo,
Saad Megahed
et al.

Abstract: Carbon nanodots with opposite chirality possess the same major physicochemical properties such as optical features, hydrodynamic diameter, and colloidal stability. Here, a detailed analysis about the comparison of the concentration of both carbon nanodots is carried out, putting a threshold to when differences in biological behavior may be related to chirality and may exclude effects based merely on differences in exposure concentrations due to uncertainties in concentration determination. The present study ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 92 publications
1
27
0
Order By: Relevance
“…An in vitro study by Duan et al showed that BSA adsorbed on GO weakened the interaction between the phospholipid membrane of A549 cells and the surface of GO, which subsequently reduced its uptake [ 96 ]. These results are also in union with the findings of higher uptake of CDs by THP-1 macrophages in serum-free conditions [ 97 ]. In another study, the authors confirmed a significant decrease of cytotoxic effects of blood protein loaded GO [ 98 ].…”
Section: Recognition and Uptakesupporting
confidence: 90%
“…An in vitro study by Duan et al showed that BSA adsorbed on GO weakened the interaction between the phospholipid membrane of A549 cells and the surface of GO, which subsequently reduced its uptake [ 96 ]. These results are also in union with the findings of higher uptake of CDs by THP-1 macrophages in serum-free conditions [ 97 ]. In another study, the authors confirmed a significant decrease of cytotoxic effects of blood protein loaded GO [ 98 ].…”
Section: Recognition and Uptakesupporting
confidence: 90%
“…[19,20] These are, in fact, key properties to push forward the applications of CNDs in many fields, ranging from sensing to catalysis. [21][22][23][24][25][26][27] Strikingly, a simple, fast and straightforward NMR analysis may often reveal that the properties of interest arise from molecular species present as impurities rather than from CNDs.…”
mentioning
confidence: 99%
“…The approach has been applied for the detection of various cations, anions and small molecules. [163][164][165] For instance, due to the binding of metal ions by CDs, electrons are transferred from CDs to the empty d orbitals of metal ions, leading to fluorescence quenching. Several studies have identified specific surface functional groups of CDs that can coordinate metal ions (such as Cu 2þ and Fe 3þ ) in biological systems.…”
Section: On-off Mechanismmentioning
confidence: 99%